Being mortal : medicine and what matters in the end - Gawande, Atul (Metropolitan Books, Henry Holt and Company, 2021)
Medicine has triumphed in modern times, transforming the dangers of childbirth, injury, and disease from harrowing to manageable. But when it comes to the inescapable realities of aging and death, what medicine can do often runs counter to what it should. Through eye-opening research and gripping stories of his own patients and family, practicing surgeon Atul Gawande reveals the suffering this dynamic has produced. Nursing homes, devoted above all to safety, battle with residents over the food they are allowed to eat and the choices they are allowed to make. Doctors, uncomfortable discussing patients' anxieties about death, fall back on false hopes and treatments that are actually shortening lives instead of improving them. but a good life-all the way to the very end.